Probation Under Quarantine: The Impact of COVID-19 on Probation in Alameda County. Issue 5 (20th October 2022) - Debus-Sherrill, Sara; Breno, Alex; Garcia, Alexandria; Clubb, Audrey C.; Chavez, Laura Agnich; Still, Wendy
ABSTRACT: In 2020, the COVID-19 pandemic rapidly changed how organizations had to operate to decrease public health risk. Consequently, COVID-19 had substantial impacts on probation organizations, their staff, and the clients they serve. The current study examines how this pandemic affected one California probation agency. Using administrative data (n = 36 months) and staff surveys (n = 216), the study found that COVID-19 affected population trends, changed the composition of probation client populations, caused wide-ranging challenges for clients, and affected staff's wellbeing and work experiences. In particular, shifts to virtual work were a dramatic change for the agency. Lessons learned from this study can assist agencies to best support staff and clients as the pandemic continues, as well as inform future responses to public health crises and other disruptive emergencies. Experiences with virtual work can also guide future consideration of the use of virtual technology within probation spaces.